Innovation in Germany - Results of the German CIS 2006 to 2010. Background report on the Innovation Surveys 2007, 2009 and 2011 of the Mannheim Innovation Panel - Birgit Aschhoff; Elisabeth Baier; Dirk Crass; Martin Hud; Paul Hünermund; Christian Köhler; Bettina Peters; Christian Rammer; Esther Schricke; Torben Schubert; Franz Schwiebacher (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Innovation is regarded as a key driver of productivity and market growth and thus has a great potential for increasing wealth. Surveying innovation activities of firms is an important contribution to a better understanding of the process of innovation and how policy may intervene to maximise the social returns of private investment into innovation. Over the past three decades, research has developed a detailed methodology to collect and analyse innovation activities at the firm level. The Oslo Manual, published by OECD and Eurostat (2005) is one important outcome of these efforts. In 1993 both organisations have started a joint initiative, known as the Community Innovation Survey (CIS), to collect firm level data on innovation across countries in concord (with each other). The German contribution to this activity is the so-called Mannheim Innovation Panel (MIP), an annual survey implemented with the first CIS wave in 1993. The MIP fully applies the methodological recommendations laid down in the Oslo Manual. It is designed as a panel survey, i.e. the same gross sample of firms is surveyed each year, with a biannual refreshment of the sample. The MIP is commissioned by the German Federal Ministry of Education and Research (BMBF) and conducted by the Centre for European Economic Research (ZEW) in cooperation with the Fraunhofer Institute Systems and Innovation Research (ISI) and the Institute for Applied Social Science (infas). (...)
urn:nbn:de:bsz:180-madoc-432388
Keywords: 330